1998
DOI: 10.1111/j.1745-4549.1998.tb00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Atmosphere Storage and Edible Coating Effects on Storage Life and Quality of Tomatoes

Abstract: Tomatoes at pink stage maturities were coated with SemperfreshTM edible fruit coating which is composed of sucrose esters of fatty acids, sodium carboxymethyl cellulose and mono‐diglycerides of fatty acids. One group of coated and uncoated tomatoes were stored at 23 × 2C under air atmosphere, another group was stored at 12C under air atmosphere and third group was stored at 12C, 93–95% RH in a controlled atmosphere (CA) containing 3% CO2, 3% O2 and 94% N2. Samples of tomatoes were analyzed for firmness, weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 9 publications
7
25
0
1
Order By: Relevance
“…On Figure 7, it can be seen that there were significant differences on appearance, flavor, firmness, and overall acceptability of C and UC tomatoes. Other authors report similar findings: the application of a coating helps maintain texture firmness [13,29,39], color, and flavor changes [2,13,38,39], on different products such as apples, and tomatoes, using several types of coatings at ambient temperature (22 ± 2 ∘ C). The scores given by the panelists to all the attributes were between 9 and 7, which is interpreted as "excellent" to "good."…”
Section: Sensory Evaluationmentioning
confidence: 55%
See 3 more Smart Citations
“…On Figure 7, it can be seen that there were significant differences on appearance, flavor, firmness, and overall acceptability of C and UC tomatoes. Other authors report similar findings: the application of a coating helps maintain texture firmness [13,29,39], color, and flavor changes [2,13,38,39], on different products such as apples, and tomatoes, using several types of coatings at ambient temperature (22 ± 2 ∘ C). The scores given by the panelists to all the attributes were between 9 and 7, which is interpreted as "excellent" to "good."…”
Section: Sensory Evaluationmentioning
confidence: 55%
“…In the same trial, higher values of TA were also reported in uncoated than in coated tomatoes. The higher TA values on uncoated samples than on coated ones were attributed to the loss of citric acid in tomatoes as fruit ripened [13,38]. …”
Section: Total Aciditymentioning
confidence: 98%
See 2 more Smart Citations
“…Weight loss of fresh tomato is primarily due to transpiration and respiration. Water is lost by transpiration due to differences in vapour pressure of water in atmosphere and tomato surface (Tasdelen and Bayindirli, 1998). Respiration causes weight reduction because a carbon atom is lost from the fruit each time a CO 2 molecule is produced from an absorbed oxygen molecule and evolved into the atmosphere (Bhowmik and Pan, 1992).…”
Section: Physiological Weight Loss (Pwl) Of Treated Tomato Samplesmentioning
confidence: 99%